Development and validity of a fern species diversity in Semirang Waterfall Area e-encyclopedia for biodiversity material for high school students - Khairunnisa', Hafidha; Anggraito, Yustinus Ulung (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2026)
The Semirang Waterfall area in Ungaran is a tourist spot with potential as a location for biodiversity research. This study aims to analyze the validity, readability, and response of students and teachers to the developed media, namely the E-Encyclopedia. A 1 x 1 m square was used for quantitative data collection at the research site, which was divided into four stations, namely around the waterfall, the middle of the climbing path, and the beginning of the climbing path. The qualitative data collected consisted of the characteristics and habitat conditions of each species. The development of learning media was carried out using guidelines from the Alessi & Trollip research and development model. The feasibility scores obtained were in the high category for material validation (0.92), media (0.98), and learning tools such as teaching modules and assessments (1.00), also student worksheets (0.80). The readability test percentage showed that the media enabled students to learn independently (98.89%). The response test involving teachers (93.33%) and students (93.33%) showed a positive category. These findings indicate that the E-Encyclopedia has a category for each test result that is good and positive. This allows the E-Encyclopedia to be used in learning process. This research contributes to the provision of up-to-date data on the composition and diversity of understory ferns in the Semirang Waterfall area and presents a model for integrating local biodiversity research results into context-based digital learning media that supports the strengthening of science process skills and in-depth learning in accordance with the Merdeka Curriculum.Abstrak. Kawasan Air Terjun Semirang, Ungaran merupakan salah satu lokasi wisata yang berpotensi sebagai lokasi penelitian kenakeragaman hayati. Penelitian ini bertujuan untuk menganalisis validitas, keterbacaan, serta respon peserta didik dan guru terhadap media yang dikembangkan yaitu E-Ensiklopedia. Kuadrat 1 x 1 m digunakan untuk pengambilan data kuantitatif di lokasi penelitian yang terbagi menjadi empat stasiun yaitu sekitar air terjun, jalur tengah pendakian, dan jalur awal pendakian. Pengembangan media pembelajaran dilakukan menggunakan panduan dari model penelitian dan pengembangan Alessi & Trollip. Skor kelayakan yang didapatkan berada pada kategori tinggi baik untuk validasi materi (0,92), media (0,98), maupun perangkat pembelajaran seperti modul ajar, asesmen (1,00), dan LKPD (0,80). Persentase dari uji keterbacaan menunjukkan bahwa media memungkinkan peserta didik untuk belajar secara mandiri (98,89%). Uji respons yang melibatkan guru (93,33%) dan peserta didik (93,33%) menunjukkan kategori positif. Temuan tersebut menunjukkan bahwa E-Ensiklopedia memiliki kategori untuk setiap hasil uji coba baik dan positif. Hal tersebut memungkinkan E-Ensiklopedia digunakan saat pembelajaran. Penelitian ini berkontribusi pada penyediaan data terkini mengenai komposisi dan keanekaragaman paku bawah di kawasan Air Terjun Semirang serta menghadirkan model integrasi hasil riset biodiversitas lokal ke dalam media pembelajaran kontekstual berbasis digital yang mendukung penguatan keterampilan proses sains dan pembelajaran mendalam sesuai Kurikulum Merdeka.